Measuring Job-Related Situational Strength and Assessing Its Interactive Effects With Personality on Voluntary Work Behavior - Meyer, Rustin D.; Dalal, Reeshad S.; José, Irwin J.; Hermida, Richard; Chen, Tiffani R.; Vega, Ronald P.; Brooks, Charlie K.; Khare, Vivek P. (Journal of Management, 2014)
Situational strength has long been viewed as a useful way of conceptualizing and predicting person–situation interactions. Some have recently argued, however, that more rigorous empirical tests of its behavioral influence are sorely needed. The current article begins addressing this literature gap by (a) developing the Situational Strength at Work (SSW) scale, (b) examining the ways in which individual differences influence perceptions of situational strength, and (c) testing situational strength’s moderating effects on two types of voluntary work behavior (i.e., organizational citizenship behavior and counterproductive work behavior). Results indicate strong psychometric properties for the SSW (thereby facilitating future organizational research on situational strength), support for theoretically based predictions regarding the role of individual differences in perceptions of situational strength, support for theoretically based moderator effects on organizational citizenship behavior, and the presence of countertheoretical (yet strong and consistent) moderator effects on counterproductive work behavior. Thus, this study makes several contributions to the situational strength literature but also reveals important areas for future theoretical development and empirical research.